ANALISIS DAN PERANCANGAN SISTEM INFORMASI PROMOSI BERBASIS WEB PADA CV.AGUNG JAYA BERSAMA - Oktafianti, Ely; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2020)
CV. Agung Jaya Bersama is one of the businesses engaged in the production of furniture from wood.Companies in carrying out promotional activities are still a simple way, namely through the distribution ofbrochures and delivery of information word of mouth from the company to the public. So that thispromotional activity is felt to be not optimal, because it has not been able to reach a wider target market andcustomers / prospective customers are still having difficulty in obtaining product information owned by thecompany. Therefore, this research aims to provide solutions to problems that occur by offering system designWeb-based promotion information where the author designs the system uses a model language approachusing use case diagrams, activity diagrams, and class diagrams. This research resulted in a prototypeanalysis system design and web-based promotional information system design on CV. Agung Jaya Bersama ..This prototype needs to be developed for further research so that it can be implemented by completing thedata security system and notification features.